Irradiation effects of swift heavy ions on palladium films deposited on 6H-SiC substrate - Thabethe, T.T.; Nstoane, T.; Biira, S.; Njoroge, E.G.; Hlatshwayo, T.T.; Skuratovd, V.A. (Nuclear Inst. and Methods in Physics Research B, 2019)
The irradiation effect of swift heavy ions on palladium (Pd) films deposited on 6H-SiC was investigated. The samples were irradiated by Xe26+ ions with the energy of 167 MeV at fluences of 1×1013 cm−2 and 3×1014 cm−2 at room temperature. Phase identification, residual stress and surface morphology were investigated with X-ray diffraction (XRD) and scanning electron microscopy (SEM). The XRD results showed that the as-deposited sample was composed of Pd and SiC with no evidence of a reaction between Pd and SiC. No reaction was observed for the lower irradiation fluence, only an increase in the Pd peak intensities was observed indicating improvement in the crystallinity of the material. A reaction between Pd and SiC forming PdSi and Pd2Si was observed after irradiation at a fluence of 3×1014 cm−2. The stress measurements indicated that the films were having tensile and biaxial stress not exceeding 200 MPa. A decrease in stress values was observed with an increase in irradiation fluence. The surface morphology of the as-deposited was flat and composed of small granules. There was an increase in granule sizes due to irradiation at 1×1013 cm−2. Irradiating at 3×1014 cm−2 caused grain agglomeration and clustering.
Keywords: Palladium; SiC; Swift heavy ions; Irradiation; Stress